ANALISIS EFEKTIVITAS GAMIFIKASI BERBASIS ZEP QUIZ TERHADAP HASIL BELAJAR SISWA SMA - Fitria, Siska Sukma Ayu Liatul Fitria; Inarotul Caturmufidarini; Erika Fataa Cahyaningrum; Jarot Tri Bowo Santoso; Kardiyem (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effectiveness of implementing Zep Quiz–based gamification in improving the learning outcomes of Grade X students in Economics at a public senior high school in Tuban. The research method employed an experimental One Group Pretest–Posttest design with a quantitative approach. The research sample consisted of 30 students. The results showed a significant difference between pretest and posttest scores, with a significance value of 0.000. The N-Gain value of 0.5728 indicates a moderate level of effectiveness. These findings demonstrate that the use of Zep Quiz is effective in enhancing students’ learning outcomes, supported by its engaging visual appearance and interactive features. Overall, Zep Quiz is suitable to be used as a modern evaluation medium capable of overcoming boredom in conventional learning. Future studies are recommended to employ an experimental design with a control group so that the effects of Zep Quiz can be compared more comprehensively, to integrate Zep Quiz with other learning methods, and to implement it not only for learning evaluation but also for improving students’ understanding of Economics learning materials.